BENCHMARKS soil sampling protocol : Guidelines for agricultural and forest systems - Symanczik, Sarah; Lori, Martina; Bacq-Labreuil, Aurélie; Beriot, Nicolas; Berlin, Alexander; Bünemann, Else K.; Cheval, Pénélope; Creamer, Rachel; Cunha, Luís; David, Felix; Di Lonardo, Paolo; Götzinger, Sophia; et al. (Luonnonvarakeskus, 2025)
This document presents a comprehensive sampling protocol to address spatial heterogeneity and variability of soil health indicators (SHI) across a site. Geo-referenced sampling points are identified using K-means sampling and integrating satellite and terrain data and existing data from the site to determine the sampling clusters. In addition, a random sample is obtained within the site. The sample numbers are tailored to the sampling area. To evaluate soil health, a diverse set of biological, chemical, and physical SHIs is proposed. To optimize soil samples for subsequent analyses, SHI-compliant sampling protocols are implemented, aligning with the BENCHMARKS sampling scheme. For baseline site characterisation, soil samples will be collected using BENCHMARKS protocols for bulk soil, bulk density, earthworms, and mesofauna. Depending on site-specific challenges, additional samples may be collected using protocols tailored to plastic sampling or hydraulic property sampling. The document also provides detailed guidelines on sample processing, shipping, and storage tailored to each soil sampling protocol. Lastly, it outlines the SHIs recommended for assessment both in the laboratory and directly in the field.
Keywords: BENCHMARKS soil sampling protocols; soil sample processing; sample storage; sample shipment; soil health indicators; laboratory analysis; variance sampling; sampling design